2023
DOI: 10.1111/inr.12831
|View full text |Cite
|
Sign up to set email alerts
|

Stress among nursing students in Vietnam: Prevalence and associated factors

Abstract: AimTo describe stress and analyze its associated factors among nursing students.IntroductionStress is a common mental health problem among medical students, especially nursing students. Therefore, understanding stress and its associated factors is necessary to improve stress in students.MethodsA cross‐sectional study was conducted among 300 nursing students using the stratified sampling method. This study used questionnaires such as demographic form, the Depression Anxiety Stress Scale 21, and the Stressors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In addition, a study by N. Ngoc, N. Tuan (2024) showed that almost half of nursing students experienced stress at different levels, which was caused by financial factors, education, clinical problems and uncertainty (Ngoc, Tuan, 2024). To this are added the difficulties with independent online training of students of medical professions (Xu, et al, 2024).…”
Section: вступmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study by N. Ngoc, N. Tuan (2024) showed that almost half of nursing students experienced stress at different levels, which was caused by financial factors, education, clinical problems and uncertainty (Ngoc, Tuan, 2024). To this are added the difficulties with independent online training of students of medical professions (Xu, et al, 2024).…”
Section: вступmentioning
confidence: 99%
“…Окрім цього, в дослідженні N. Ngoc, N. Tuan (2024) показано, що майже половина студентів медсестер відчували стрес на різних рівнях, причиною якого були фінансові фактори, освіта, клінічні проблеми та невпевненість (Ngoc, Tuan, 2024). До цього додаються і трудності з самостійним онлайн навчанням студентів медичних професій (Xu, et al, 2024).…”
Section: вступunclassified
“…Moderate levels of stress have been reported among majority of student nurses in Philippine [11], Spain [7], India [27], Malawi [28] and Northern Nigeria [22]. Studies in Vietnam [29] and Calabar, South-South Nigeria [21], reported high levels of stress among majority of the students studied, while a study in South-West Nigeria reported a low level of stress [20]. A meta-analysis involving 2 countries in Europe, 2 in Asia, and Saudi Arabia, also reported stress levels of intern nurses to be moderate [30], while a systematic review in Middle East and North Africa reported the prevalence range of low perceived stress of 0.8-65%, moderate stress of 5.9-84.5%, and high stress of 6.7-99.2% [31].…”
Section: Correlation Of Stress Indices and Socio-demographic Characte...mentioning
confidence: 99%